Effect of Different Wine-Making Techniques on the Composition and Quality of Pinotage Wine. I. Low-Temperature Skin Contact Prior to Fermentation - Marais, J. (South African Journal of Enology and Viticulture, 2017)
The effect of low-temperature skin contact prior to fermentation (1, 2 and 4 days at 10°C and 15°C, respectively) on Pinotage wine composition and quality was investigated over four seasons (1999 to 2002). The extraction of total polyphenols (total flavonoids, total tannins and total anthocyanins) was followed during skin contact and fermentation.  Wines were analysed for total polyphenols and esters, and sensorially evaluated for Pinotage cultivar character (berry/plum) intensity and overall wine quality. Polyphenol extraction rates differed greatly between the skin contact treatments. Polyphenol concentrations in the final wines increased slightly with an increase in prefermentation skin contact tune. Acetate ester concentrations generally decreased with an increase in prefermentation skin contact time. Wine quality differed significantly between some treatments and the most typical and highest quality Pinotage wines were produced by prefermentation skin contact for 4 days at 10°C and the lowest by the control and skin contact for 4 days at 15°C.